PEMBENAHAN SIFAT FISIKA TANAH OXISOL DENGAN PERLAKUAN KOMPOS (Revamping The Physical Properties of Oxisol Soil With Compost Treatment) - Hana Basyirah Simbolon; Sumono Sumono; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT   Soil physics is an important factor for plant growth. This research was to know the effect of organic matter on the physical properties of oxisol soil. The study used a completly non factorial randomized design, consisting of 6 treatments and 3 replications, ie K1 (no compost), K2 = 9 kg of soil oxisol + 1 kg of compost, K3 = 8 kg of soil oxisol + 2 kg compost, K4 = 7 kg of soil Oxisol + 3 kg compost, K5 = 6 kg of soil oxisol + 4 kg of compost, K6 = 5 kg of oxisol soil + 5 kg of compost. Parameters observed included soil texture, organic matter, soil thickness, porosity, soil pore size, permeability, moisture content at field water, available water. The results showed that oxisol soil type was clay, soil organic material ranged from 0,36 to 4,60%, soil thickness ranged from 18,71 to 24,50 cm, porosity ranged from 24,50 to 45.30%, soil pore size was 4,84 to 7,10 μm, permeability ranges from 0.03 to 1.14 cm /hour, moisture content at field capacity at pF 2,54 ranged from 37,26 to 45,06%, pF 4.2 ranged  from 27,65 to 35,44%  so that the  water availability was 9,62 – 12,96 %.   Keywords: Physical Properties Of Soil, Oxisol, Compost ABSTRAK Sifat fisika tanah merupakan salah satu faktor penting bagi pertumbuhan tanaman. Penelitian ini untuk mengetahui pengaruh pemberian bahan organik  terhadap sifat fisik tanah oxisol. Penelitian menggunakan rancangan acak lengkap non faktorial, terdiri dari 6 perlakuan dan 3 ulangan, yaitu K1 (tanpa kompos), K2= 9 kg tanah oxisol + 1 kg kompos, K3= 8 kg tanah oxisol + 2 kg kompos, K4= 7 kg tanah oxisol + 3 kg kompos, K5= 6 kg tanah oxisol + 4 kg kompos, K6= 5 kg tanah oxisol + 5 kg kompos. Parameter yang diamati meliputi tekstur tanah, bahan organik, tebal tanah, porositas, ukuran pori tanah, permeabilitas, kadar air kapasitas lapang, air tersedia. Hasil penelitian menunjukkan jenis tanah oxisol adalah liat, bahan organik tanah berkisar antara 0,36 ‒ 4,60%, tebal tanah berkisar antara 18,71 ‒ 24,50 cm, porositas berkisar antara24,50 ‒ 45,30%, ukuran pori tanah berkisar antara 4,84 ‒ 7,10 ,  permeabilitas berkisar antara 0,03 ‒ 1,14 cm/jam, kadar air kapasitas lapang pada pF 2,54 berkisar antara37,26 ‒ 45,06%, pF 4,2 berkisar antara 27,65 ‒ 35,44% sehingga air tersedia 9,62 ‒ 12,96%.   Kata Kunci: Sifat Fisika Tanah, Oxisol, Kompos